PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Transportasi Di Indonesia Tahun 2017-2019) - Bella Anggraini; Widi Hariyanti; Faiz Rahman Siddiq (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study is to analyze whether the board of commissioners is independent, komiteaudit, institutional ownership, managerial ownership which is a component of corporate governance towards profit management with moderation of profitability (Study on Transportation Companies in Indonesia Year 2017-2019). Sampling techniques using motedo purpose sampling. This study used 78 transportation companies listed on the Indonesia Stock Exchange in 2017-2019.The method used in this study was simple linear regression and Moderated Regression Analysis (MRA). The results of this study are:1) the independent board of commissioners has an influence on profit management, 2) the audit committee has no influence on profit management, 3) institutional ownership has no effect on profit management, 4) managerial ownership affects profit management practices, 5) profitability cannnot moderate the influence of the independent board of commissioners on profit management, 6) profitability cannot moderate the influence of the audit committee on profit management, 7) profitability cannot moderate the influence of institutional ownership on profit management, 8) profitability cannot moderate the influence of managerial ownership on profit management. Keywords: Corporate Governance, Profitability, Profit Management, Transportation Companies